Foundations of Parasitology - Roberts Larry (McGraw-Hill Science/Engineering/Math, 2004)
A parasitology text for biology and/or zoology students at the undergraduate level. Emphasizes principles with related information on the biology, physiology, morphology, and ecology of the major parasites of humans and domestic animals. This is not a diagnostic manual for medical students.